Pelatihan Basic Typography Digital Menggunakan Software Adobe Illustrator Bagi Siswa SMK Muhammadiyah 1 Kota Palembang - Hestia Rachmat Nunciata Lubis; Bobby Halim; Yosef Yulius; Fifin Salsabila; Melda Tiana (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Vocational High School students, particularly who majoring in Visual Communication Design, often encounter difficulties in understanding and applying fundamental typography principles such as choosing right font, size, letter spacing, and layout. Furthermore, despite familiarity with design software, many students have yet fully master the features related to typography. This training aims to enhance both comprehension and practical skills of SMK Muhammadiyah 1 Palembang students in digital typography through the utilization of Adobe Illustrator software. The training materials cover typography introduction, the selection of appropriate fonts, layout arrangement and their application in Visual Communication Design. The training methods employed include demonstrations, practice and group discussions. The result of the typography training show a considerable improvement in students’ understanding and ability to create attractive and professional magazine cover as an outcome. This initiative is anticipated to equip students with the relevant skills to the needs of current creative industry in digital era.